Affectionless control: A parenting style associated with obesity and binge eating disorder in adulthood - Amianto, Federico; Martini, Matteo; Olandese, Francesco; Davico, Chiara; Abbate‐Daga, Giovanni; Fassino, Secondo; Vitiello, Benedetto (European eating disorders review, 2021)
Objective Obesity is rising globally with a heavy health and economic burden. Early attachment experiences are relevant to the development of obesity. The purpose of this study was to investigate if parental care and attachment style experienced in childhood is associated with obesity, with or without binge eating disorder (BED), in adulthood. Method Parental style, personality traits, and psychopathology were assessed in 810 clinically referred adults with obesity, of whom 357 with BED and 453 without BED (non‐BED), and 463 healthy subjects (HS). Assessments included the Parental Bonding Instrument, Temperament and Character Inventory, Eating Disorder Inventory‐2, Symptom Checklist‐90 and Beck Depression Inventory‐II. Results Both BED and non‐BED reported lower maternal and paternal care and higher overprotection than HS. BED reported worse levels of parental care than non‐BED and HS. ‘Affectionless control’ parenting style was more frequently reported by both BED and non‐BED than HS. No significant differences in parenting style emerged between BED and non‐BED. Conclusions Perception of parental ‘affectionless control’ was associated with obesity in adults, and lower quality of parental care was more frequently reported by participants with BED. Parental style may constitute an important target for early interventions to prevent obesity. Highlights Perceived affectionless control is a specific parenting trait associated with obesity Affectionless control in both parents was linked to a 9‐fold greater risk of obesity Binge eating disorder (BED) was not characterized by specific parental styles with respect to non‐BED